Relationship between mechanical amorphization and boron integration during processing of FeNbB alloys - Ipus, J; Blázquez, J; Conde, C; Borrego, J; Franco, V; Lozano-Pérez, S; Conde, A (2014)
Fe75Nb10B15 alloys were prepared by mechanical alloying using different boron powders (crystalline B, commercial amorphous B, optimized amorphous B and intermetallic FeB) in the initial mixture in order to study the boron incorporation into the Fe matrix and its influence on the amorphization of the alloys. Another composition with the same Fe/Nb ratio but without boron was prepared in order to differentiate between the influence of B and Nb in the evolution of microstructure and magnetic properties. Amorphization of samples was followed by X-ray diffraction and Mössbauer spectroscopy, concluding that only B-containing alloys develop an amorphous phase, while for the B-free alloy a supersaturated solid solution was observed as the final microstructure. Nb is rapidly incorporated into the matrix whereas remaining B inclusions are found at the end of the explored milling range for all B-containing samples. The amount of dissolved boron into the amorphous matrix was estimated from magnetic measurements, being the alloy prepared using FeB powder the one that most effectively dissolves this element. © 2014 Elsevier Ltd. All rights reserved.